Foreign investment regulation and firm productivity: Granular evidence from Indonesia - Robert Genthner; Krisztina Kis-Katos (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2019)
Countries that control foreign direct investment (FDI) often face the trade-off between following national policy interests and suffering efficiency losses arising from FDI restrictions. We demonstrate the presence of this trade-off in the case of a protectionist FDI policy in Indonesia that restricts FDI at the product level. Using a yearly census of Indonesian manufacturing firms for 2000 to 2015, we link productlevel changes in FDI regulation to changes in firm-level productivity. Controlling for an extensive set of fixed effects as well as potential political-economy drivers of regulation, we find that newly introduced limitations on FDI were successful at reducing foreign capital use within the regulated firms. Although the drop in foreign capital has been more than compensated by increases in domestic capital, regulated firms have experienced a substantial loss in productivity that was concentrated in the sectors most dependent on external finance and technological innovation.
Keywords: F23; L51; D24; F21; L6; 330; FDI regulation; Indonesia; productivity